TECHNOLOGY-BASED ISLAMIC EDUCATION LEARNING FACILITIES DURING THE PANDEMIC AT SDIT AL MUMTAZ JAYANTI TANGERANG - Mumu Zainal Mutaqin; Mohamad Erihadiana; Qiqi Yulianti Z; Solihin Solihin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
Schools need to ensure that learning activities continue even though students are at home because it requires technology that supports the learning process. The purpose of the research is that learning facilities at SDIT Al Mumtaz are used so that teachers use learning-based facilities to facilitate the learning process. This research uses a qualitative approach with a descriptive approach. The data collection techniques are through observation, interviews and documentation. Data analysis was obtained through notes, observations, interviews, and documentation, then the data obtained were then analyzed. Data analysis is carried out through three activity lines that occur simultaneously, namely data reduction, data presentation, conclusion drawing or verification. The results of this study indicate that the learning facilities at SDIT Al Mumtaz have implications for changes in student behavior in terms of attitudes, knowledge and skills. Students are assessed thoroughly and objectively according to the student's condition. The use of technology during this pandemic is an alternative so that students are motivated in learning. As for the expectations of parents for learning during the pandemic to be more attractive in using learning technology during the pandemic to be more attractive in utilizing learning technology.